A voxel‐based morphometry and diffusion tensor imaging analysis of asymptomatic Parkinson's disease‐related G2019S LRRK2 mutation carriers. Issue 6 (30th January 2014) - Thaler, Avner; Artzi, Moran; Mirelman, Anat; Jacob, Yael; Helmich, Rick C.; van, Bart F.L.; Gurevich, Tanya; Orr‐Urtreger, Avi; Marder, Karen; Bressman, Susan; Bloem, Bastiaan R.; Hendler, Talma; et al.
ABSTRACT Background Patients with Parkinson's disease have reduced gray matter volume and fractional anisotropy in both cortical and sub‐cortical structures, yet changes in the pre‐motor phase of the disease are unknown. Methods A comprehensive imaging study using voxel‐based morphometry and diffusion tensor imaging tract‐based spatial statistics analysis was performed on 64 Ashkenazi Jewish asymptomatic first degree relatives of patients with Parkinson's disease (30 mutation carriers), who carry the G2019S mutation in the leucine‐rich repeat kinase 2 (LRRK2) gene. Results No between‐group differences in gray matter volume could be noted in either whole‐brain or volume‐of‐interest analysis. Diffusion tensor imaging analysis did not identify group differences in white matter areas, and volume‐of‐interest analysis identified no differences in diffusivity parameters in Parkinson's disease‐related structures. Conclusions G2019S carriers do not manifest changes in gray matter volume or diffusivity parameters in Parkinson's disease‐related structures prior to the appearance of motor symptoms. © 2014 International Parkinson and Movement Disorder Society